2020
DOI: 10.3390/antibiotics9120873
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Action and Reversal of Resistance in MRSA by Difluorobenzamide Derivatives Targeted at FtsZ

Abstract: The bacterial cell division protein, FtsZ, has been identified as a target for antimicrobial development. Derivatives of 3-methoxybenzamide have shown promising activities as FtsZ inhibitors in Gram-positive bacteria. We sought to characterise the activity of five difluorobenzamide derivatives with non-heterocyclic substituents attached through the 3-oxygen. These compounds exhibited antimicrobial activity against methicillin resistant Staphylococcus aureus (MRSA), with an isopentyloxy-substituted compound sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Replacement of the amide group of 11 by isosteres gave compounds 15 – 17 with reduced inhibition ( Figure 4 A) that were also toxic to the cells. However, the addition of fluorine atoms at 2- and 6-positions of the benzamide ring of 11 (as in PC190723) rendered the 3-chloro derivative 18 ( 45 , 46 ) and the 3-trifluoromethyl analogue 20 that were both stronger competitors ( Figure 4 A) with 1.3 and 0.7 μM K D values, respectively ( Figure 5 A and Table 1 ). Compound 20 induced a marked divisomal inhibition phenotype on B. subtilis , consisting of cell filamentation and GFP-FtsZ delocalization ( Figure 5 B and Table 1 ; raw data plots in Figure S4 and statistics in Table S2 ), as well as characteristic enlarged spherical cells in S. aureus and FtsZ-mCherry delocalization ( Figure 5 C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Replacement of the amide group of 11 by isosteres gave compounds 15 – 17 with reduced inhibition ( Figure 4 A) that were also toxic to the cells. However, the addition of fluorine atoms at 2- and 6-positions of the benzamide ring of 11 (as in PC190723) rendered the 3-chloro derivative 18 ( 45 , 46 ) and the 3-trifluoromethyl analogue 20 that were both stronger competitors ( Figure 4 A) with 1.3 and 0.7 μM K D values, respectively ( Figure 5 A and Table 1 ). Compound 20 induced a marked divisomal inhibition phenotype on B. subtilis , consisting of cell filamentation and GFP-FtsZ delocalization ( Figure 5 B and Table 1 ; raw data plots in Figure S4 and statistics in Table S2 ), as well as characteristic enlarged spherical cells in S. aureus and FtsZ-mCherry delocalization ( Figure 5 C).…”
Section: Resultsmentioning
confidence: 99%
“…Replacement of the amide group of 11 by isosteres gave compounds 15 – 17 with reduced inhibition (Figure A) that were also toxic to the cells. However, the addition of fluorine atoms at 2- and 6-positions of the benzamide ring of 11 (as in PC190723) rendered the 3-chloro derivative 18 , and the 3-trifluoromethyl analogue 20 that were both stronger competitors (Figure A) with 1.3 and 0.7 μM K D values, respectively (Figure A and Table ). Compound 20 induced a marked divisomal inhibition phenotype on B.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in the past on the effects of PC190723 on E. coli have been confusing, with a few reports suggesting an effect on FtsZ polymerization resulting in cell filamentation (Kaul et al, 2014), while others did not find any effect on EcFtsZ (Anderson et al, 2012; Andreu et al, 2010; Khare et al, 2019). The outer membrane has been shown to be a permeability barrier for PC190723 in E. coli (Chai et al, 2020; Khare et al, 2019). In addition, the Resistance-Nodulation-Division (RND) family of efflux pumps has been attributed to resistance against 2,6-difluorobenzamide derivatives, including TX436 (a prodrug of PC190723) in Gram -ve bacteria (Kaul et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…FtsZ was found to be delocalised into patches all over the cell or multiple Z-rings at unusual sites in the cell. As a key element for cell division, FtsZ is a focus target for antibacterial treatments [ 32 , 33 , 34 , 35 , 36 ]. As an explanation for the delocalisation, Strahl and Hamoen (2010) showed that the FtsZ guiding proteins FtsA and MinD are inactivated after loss of the membrane potential.…”
Section: Discussionmentioning
confidence: 99%